Peningkatan Kemampuan Numerasi Siswa Sekolah Dasar melalui Implementasi Model Pembelajaran Berbasis Proyek (PjBL) pada Muatan Pelajaran IPAS - Atika Dewi; Nur Fajrie; Irfai Fathurohman (Journal Prakarsa Paedagogia, 2024)
The aim of this study is to enhance numeracy skills through improving the quality of PjBL. This learning model can be applied in all subject contents, including Natural and Social Sciences. PjBL or project-based learning is a key strategy for improving students' numeracy skills. Looking at the results of the 2023 Education Report Card, the numeracy achievement results of elementary school students are still classified as moderate where more than 50% of students still have numeracy skills below the minimum.This classroom action research (PTK) was conducted in class V of SDN Pangkalan, involving 16 students. The research activities were carried out through two cycle processes. The research data was obtained from observation, student work, and documentation, and analyzed using observation analysis technique. The research concluded that the PjBL model effectively enhances students’ numeracy skills.